Big cats - Mills, Andrea (New York, N.Y. : DK Pub., 2019)
Introduces big cats, including lions, tigers, jaguars, leopards, and cheetahs. Find out how big cats hunt, learn about cat myths and legends, and discover where big cats live, how they move, and more.
Includes index.
Map and illustrations on endpapers.
7.4
3-6.
3-6
Keywords: Felidae -- Juvenile literature; Animals; Cat family (Mammals); Animals; Wild cats